The Relationship Between Lifestyle and The Incidence Of Hypertension in Adolescents in Paccerakang Health Centres and Sudiang Health Centres In 2023 - Tereja Oktaviana Lim (Health Notions, 2023)
Hypertension is a non-communicable disease. Hypertension is not only suffered by adults and the elderly; adolescents can also suffer from hypertension. Hypertension in adolescents can increase the risk of health problems in the future. This study aimed to determine the relationship between lifestyle and the incidence of hypertension in adolescents using a cross-sectional study design. The population in this study were all residents living in the Paccerakkang Public Health Centres and The Sudiang Public Health Centres working areas. The sampling technique was a simple random sampling technique to get a research sample of 81 adolescents. The Chi-Square test results show a relationship between sleep patterns and physical activity and the incidence of hypertension in adolescents. In contrast, stress status does not have a significant relationship with the incidence of hypertension in adolescents.Keywords: Hypertension, Adolescents, Sleep Pattern, Stress Status, Physical Activity.